The Improvement On Reading Literacy (Competence) Students Of Chemistry Department-FKIP-Universitas Riau Through Students Worksheet Of English For Chemistry -Based Active Learning - Asmadi Muhamamad Noer (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstrak-English for Chemistry (called Bahasa Inggris Kimia, BIK in Indonesia) is a mandatory course which is supported students professional of student support department of chemistry or chemistry teacher candidates in order to increasing mastery the contents (chemistry). Development Method of teaching materials course (also called Students worksheet, called LKM: Lembar Kegiatan Mahasiswa) followed the design of Plomp. Plomp design consists of three stages such as: a preliminary study (analysis of the needs and characteristics of learners), Products (prototype) and Evaluation (validation of the product). After prototype instructional materials formed, it pay attention to analysis of matching the needs and characteristics of students, then the product validation both self-evaluation and validation by experts have been conducted. Validated is by Contents specialist (chemical education experts) and expert in English. All inputs and suggestions suitable is accommodated in order to produce a product appropriately used by learners. The results of product testing of LKM on a freshman-2014/2015 shows the students are motivated to learn by way of active learning. Keyword: chemistry English language (English for chemistry), student worksheet of active learning